Concurrent Structural and Functional Patterns in Patients With Amnestic Mild Cognitive Impairment - Liu, Li; Wang, Tenglong; Du, Xiangdong; Zhang, Xiaobin; Xue, Chuang; Ma, Yu; Wang, Dong (Frontiers in Aging Neuroscience, 2022)
Amnestic mild cognitive impairment (aMCI) is a clinical subtype of MCI, which is known to have a high risk of developing Alzheimer’s disease (AD). Although neuroimaging studies have reported brain abnormalities in patients with aMCI, the concurrent structural and functional patterns in aMCI patients were still unclear. In this study, we combined Voxel-Based Morphometry (VBM), Amplitude of Low-Frequency Fluctuations (ALFF), Regional Homogeneity (Reho) and Resting-State Functional Connectivity (RSFC) approaches to explore the concurrent structural and functional alterations in aMCI patients. We found that compared with healthy controls, both ALFF and Reho were decreased in the right superior frontal gyrus (SFG_R) and right middle frontal gyrus (MFG_R) of aMCI patients, and both gray matter volume (GMV) and Reho were decreased in the left inferior frontal gyrus (IFG_L) of aMCI patients. Furthermore, we took these overlapping clusters from the VBM, ALFF and Reho analysis as seed regions to analyze the RSFC. We found that aMCI patients had decreased RSFC between the SFG_R and right temporal lobe (sub-gyral) (TL_R), between the MFG_R seed and left superior temporal gyrus (STG_L), left inferior parietal lobule (IPL_L), and right anterior cingulate cortex (ACC_R), between the IFG_L seed and left precentral gyrus (PRG_L), left cingulate gyrus (CG_L), and IPL_L, compared with healthy controls. These findings highlighted the shared imaging features in structural and functional magnetic resonance imaging, suggesting that SFG_R, MFG_R and IFG_L may play a major role in the pathophysiology of aMCI, which might be useful for better understanding the underlying neural mechanisms of aMCI and AD.